Role of Ultrasound-guided Tru-cut Needle Biopsy in the Diagnosis of Suspicious Breast Masses at South Valley University Hospitals - Ghada M. Abd ElRazik; Dalia Besharii Hamada; Mohammed M. Mubarak; Ahmed M. Khalaf-Awad (SVU - International Journal of Medical Sciences)
Background: The global increase in breast cancer emphasizes early detection through screening and improved molecular subtype understanding. Mammography and ultrasound identify non-palpable lesions, and core needle biopsy aids in definitive surgery planning. Objectives: Evaluate ultrasound-guided Tru-cut needle biopsy in suspicious breast masses, analyzing procedure results, histopathological findings, and their correlation with imaging data. Patients and methods: A cross-sectional study at Qena University Hospitals focused on females aged 20-70 with clinically suspected breast lesions. Ultrasound using a 7.0-MHz transducer examined variables, and core needle biopsy data included coagulation tests, needle details, and Stereotactic Biopsy Device usage. Results: Participants (mean age 50.9 ± 10.1 years) had palpable masses (96%), mainly on the right, and 84% used ultrasound. Lesions (16.5 ± 14.5 cm) were often in the upper outer quadrant, with 76% malignant (invasive duct carcinoma). Needle types included semi-automatic 14 G (56%). Biopsies yielded 4.5 ± 1.0 cores. Histopathology showed 24% benign lesions and 76% malignant. Ultrasound demonstrated 94.7% sensitivity, 100% specificity, and 95% accuracy. Conclusion: Ultrasound-guided Tru-cut needle biopsy is vital for diagnosing breast tumors, demonstrating high sensitivity, specificity, and accuracy, supporting its role in timely and precise breast cancer diagnosis, influencing patient management and treatment decisions.